Systems and procedures and work study on H & A International Inc. - Abad, George, II; Alcasabas, Ramon; Irong, Elton Cris; Montañez, Mario V., II (College of Engineering, 1998)
H&A International, Inc. a company specializing in making stuff toys, dolls and bags were chosen by the group as the site in order to conduct work study techniques. The company currently has a job order of 70 thousand beachbags from AVON, and is producing them since last December 1997. The group has documented the company's present system; the company's production line plant comprises of four lines, namely cutting, sewing, finishing and product development area, with the sewing area having the most bearing among the four, in terms of operations. The general specifications for each line were taken, included were line layout, machine and manpower complement. H & A International, Inc. currently has hired 138 workers in its current production of beach bags, majority of which are deployed in the sewing section. The company has various equipment to furnish its production lines, with the single needle sewing machine as its most basic equipment with regards to the sewing section. Other equipment were also added to the company's machine compliment roster, including the double needle sewing machine needed to make the work faster, specifically in producing the topseat, which is part of the beach bag operation. The steps and elements involved were enumerated by the group and method study as well as work measurement techniques were to be applied later on. In addition, the group has also documented the company's system and procedures; basic forms were enumerated and discussed according to their use. With the present system already documented, the group analyzed the system for potential problems; the main concerns were rounded off to three, namely problems with regards to lack of management personnel, disorderly workstations, and absenteeism in the company's workforce. These three greatly contribute to the decrease in efficiency in the company's production, in general. Currently, the company is facing a tight production schedule and a number of details are being changed by the company's assistant manager in order to increase total output. The groups has come up with a number of alternatives for the three main concern, including a proposed re-organization of workstations. With regards to the new layout, it can be seen that total material flow or travel has been decreased sufficiently. Alternatives proposed for management and attendance problems were also given, but to a lesser detail, since these are more measured in terms of qualitative aspects. The group hopes that the alternatives given will be taken into consideration by the company, as well as to serve its production requirements.